A survey of health needs and interests of grades four, five and six pupils in the division of Nueva Ecija and their educational implication to curriculum development - Tejero, Brigida C. 1912- ([Quezon City s.n.], 1964)
This study identifies the health needs of the grades four, five, and six pupils in the Division of Nueva Ecija and the educational implication of the findings on curriculum development.
Thesis (M.Ed.)--University of the Philippines
Keywords: Health education; Hygience, Rural -- Nueva Ecija